544. Severe COVID-19 in Children and Young Adults in the Washington DC Metropolitan Region. (31st December 2020) - DeBiasi, Roberta L; Song, Xiaoyan; Ansusinha, Emily; Smith, Karen L; Bell, Michael; Pershad, Jay; Hahn, Andrea; Hamdy, Rana; Hanisch, Benjamin; Harik, Nada; Jantausch, Barbara A; Koay, Adeline; et al.
Abstract: Background: Children and young adults were initially reported as largely spared from severe complications of SARS-CoV-2 infection, but the impact to this population has been significant. Methods: This observational retrospective cohort study includes 420 symptomatic children and young adults with lab confirmed SARS-CoV-2 infection treated between March 15 and June 16, 2020 at Children's National Hospital in Washington DC. We identified and compared cohorts of non-hospitalized (N=324) and hospitalized (N=96) patients, including non-critically ill (N=64) and critically ill hospitalized (N=32) patients. Clinical and demographic data were extracted from medical records Results: Of 420 SARS-CoV-2-infected symptomatic patients, 23% required hospitalization, of which 67% were non-critically ill and 33% were critically ill. All age groups were represented in the symptomatic cohort, with a median age of 8.6 years. Patients > 15 years of age represented 44% of critical care admissions. Males and females were equally represented in all cohorts. Underlying medical conditions were present in 36%, but more common in hospitalized (59 %) and critically ill (66 %) patients. The most frequent underlying diagnosis overall was asthma (16 %), but also included neurologic (6 %), diabetes (3 %), obesity (3 %), cardiac (3 %), hematologic (3 %) and oncologic (1 %) conditions. The majority (66 %) of SARS-CoV-2 infected patients presented with respiratory symptoms with or without fever. Other symptoms were also present, including diarrhea/vomiting (21 %), myalgia (11 %), chest pain (8 %) and loss of sense of smell or taste (7%). Hospitalized patients required varying levels of respiratory support, including mechanical ventilation, BiPAP, RAM cannula and HFNC. Additional presentations included diabetic hyperglycemia, sickle cell vaso-occlusive crisis, vascular complications, and multisystem inflammation. Treatment included remdesivir, convalescent plasma, tocilizumab and other therapies. Conclusion: Although children/young adults have been less affected than elderly adults, the impact of SARS-CoV2 on this population has been significant in Washington DC and informs other regions anticipating their surge. Disclosures: Andrea Hahn, MD, MS, Johnson and Johnson (Consultant)